Die psalms as himnes in "n liturgiese konteks - Vos, Casparus Johannes Adam (HTS teologiese studies, 2004)
The liturgical function of the hymns in the psalmsIn many ways the psalms fulfill a bridging function between divergent denominations that previously avoided each other. In the Hebrew text of the Psalter most of the psalms bear clear titles. None of the titles of the psalms originated together with the actual psalms. Instead, they offer instruction to the reader about the process that led to the compilation of the psalms into collection. The psalms are more than liturgy and liturgy comprises more than merely psalms. Therefore, the psalms cannot simply be clothed in liturgical vestments. Hymns that occur in the Book of Psalms form the focus of this article. It is clear that the praise in the hymns follows different patterns. The article aims to explore the liturgical function of the hymns in the psalms.